2018
DOI: 10.1002/jocb.390
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Relationship between Age, Achievement, and Creativity in Mathematics

Abstract: In this exploratory study, I investigate the relationship between age, knowledge, and creativity in mathematics, by looking at to what extent does grade level, controlled for mathematical achievement, influence mathematical creativity and what characterizes the relationship between grade level, mathematical achievement and mathematical creativity. This was accomplished in two steps. In the first part, 301 students, 184 grade eight students and 117 grade eleven students, were given a creative mathematics test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
1
0
1
Order By: Relevance
“…were not likely due to measurement error, as the tasks used have been shown to be reliable and valid in previous research (Beck et al, 2016;Dewing, 1970;Jacobs & Pierce, 1966;Okoh, 1980;Runco, 1985;Torrance, 1966). Indeed the inter-rater CHILDREN'S CREATIVITY AND BILINGUALISM -Thinking Skills and Creativity reliabilities in the present study were substantial to near perfect (Conger, 2017) and performance on tests correlated with age, vocabulary, and nonverbal IQ, as would be expected from previous research (Haavold, 2018;Lee & Therriault, 2013;Nusbaum & Silvia, 2011;Wallach & Kogan, 1965;Wu, Cheng, Ip, & McBride-Chang, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…were not likely due to measurement error, as the tasks used have been shown to be reliable and valid in previous research (Beck et al, 2016;Dewing, 1970;Jacobs & Pierce, 1966;Okoh, 1980;Runco, 1985;Torrance, 1966). Indeed the inter-rater CHILDREN'S CREATIVITY AND BILINGUALISM -Thinking Skills and Creativity reliabilities in the present study were substantial to near perfect (Conger, 2017) and performance on tests correlated with age, vocabulary, and nonverbal IQ, as would be expected from previous research (Haavold, 2018;Lee & Therriault, 2013;Nusbaum & Silvia, 2011;Wallach & Kogan, 1965;Wu, Cheng, Ip, & McBride-Chang, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…Discrimination in different grade levels: According to Hong, and Milgram (2010) life experiences like schooling have vigorous impacts on domain-specific creativity. Some researchers concluded that years of schooling was progressively contributed to student's creativity (Haavold, 2018;Sak & Maker, 2006). Therefore, in the context of criterion-related validity, firstly, the level of discrimination of participants at different grade levels (5th, 6th, 7th, and 8th grade) by the items in the test was examined.…”
Section: Criterion-related Validitymentioning
confidence: 99%
“…Getzels dan Jackson (Runco, 2007) membandingkan siswa dengan IQ tinggi dan siswa yang sangat kreatif sebab diyakini bahawa siswa yang kreatif adalah siswa yang mendalami keilmuan tertentu (Haavold, 2020). Dapat disimpulkan bahwa kelompok ber-IQ tinggi terlihat lebih diharapkan, sedangkan kelompok kreativitas tinggi yang tidak unggul secara akademis kurang diminati oleh siswa.…”
Section: Siswa Berprestasiunclassified